Toxicity of Metal Oxides, Dyes, and Dissolved Organic Matter in Water: Implications for the Environment and Human Health - Haradhan Kolya; Chun-Won Kang (Toxics, 2024)
This study delves into the critical issue of water pollution caused by the presence of metal oxides, synthetic dyes, and dissolved organic matter, shedding light on their potential ramifications for both the environment and human health. Metal oxides, ubiquitous in industrial processes and consumer products, are known to leach into water bodies, posing a significant threat to aquatic ecosystems. Additionally, synthetic dyes, extensively used in various industries, can persist in water systems and exhibit complex chemical behavior. This review provides a comprehensive examination of the toxicity associated with metal oxides, synthetic dyes, and dissolved organic matter in water systems. We delve into the sources and environmental fate of these contaminants, highlighting their prevalence in natural water bodies and wastewater effluents. The study highlights the multifaceted impacts of them on human health and aquatic ecosystems, encompassing effects on microbial communities, aquatic flora and fauna, and the overall ecological balance. The novelty of this review lies in its unique presentation, focusing on the toxicity of metal oxides, dyes, and dissolved organic matter. This approach aims to facilitate the accessibility of results for readers, providing a streamlined and clear understanding of the reported findings.